Statement (copy) : British Labour and Spain (text of letter to Foreign Secretary) - Citrine, Walter, 1887-1983
1936-10-22 015a_0004_001 COPY. "The Secretary, National Joint Council of Labour, Transport House, London. "At this decisive moment for Spain and for Europe when the enemy, not by their own strength, but exclusively by their use of armed aid from abroad, are directing their principle drive against Madrid the Spanish people greets all those workers and free men of England who in the spirit of justice are prepared to declare themselves against the monstrosity of the present situation. "I do not believe that there has been in the history of modern Europe a parallel example of an International Situation so scandalous and so suicidal. Even now in the last week while the examination of the charges brought by the Spanish Government has been in progress the rebels received on October 15th at Cadiz a new cargo of arms including tanks and flame throwers sent to them by their foreign allies exactly as though the Non-Intervention Agreement and the Committee of Control did not exist. "Madrid will not fall because the workers of Madrid and the whole people of Madrid is decided to defend the City. But it is the violations of the Pact of Non-Intervention and they alone which are responsible for the prolongation of the war and for all the blood which is being spilled in Spain as a result of the continuance of the conflict. "We send our most profound thanks to all those who in defending the cause of the Constitutional Government of Spain are at the same time defending the cause of world peace against these generals and adventurers in the service of the forces of destruction and war. (signed) ALVEREZ DEL VAYO, Commissioner General for War and Member of Parliament for Madrid. 292/946/15a/4(i)